Killer Yeasts - Cause of Stuck Fermentations in a Wine Cellar - van Vuuren, H.J.J.; Wingfield, Brenda D. (South African Journal of Enology and Viticulture, 2017)
Sluggish fermentations in five fermenters in a wine cellar were investigated. Methylene blue-stains of yeast suspensions revealed that approximately 90% of the total yeast population in each of the fermenters were dead. The viable cells in each fermenter were killer yeasts. Polyacrylamide gel electrophoresis of total soluble cell proteins showed that the same killer yeast occurred in each of the five fermenters. The effect of killer yeast on viability and fermentation activity of the wine yeast was studied in an enriched grape juice medium at 20°C and 30°C. Death rate of the wine yeast was considerably higher in the presence of the killer yeast and fermentations were retarded at both temperatures. The killer yeast induced flocculation of the non-flocculent wine yeast.